2016
DOI: 10.2175/106143015x14362865227913
|View full text |Cite
|
Sign up to set email alerts
|

Removal Rate of Organic Matter Using Natural Cellulose via Adsorption Isotherm and Kinetic Studies

Abstract: In this study, the removal of natural organic matter (NOM) using coconut fiber (CF) and palm oil fiber (POF) was investigated. Preliminary analysis was performed using a jar test for the selection of optimal medium before the fabricated column model experiment. The equilibrium studies on isotherms and kinetic models for NOM adsorption were analyzed using linearized correlation coefficient. Results showed that the equilibrium data were fitted to Langmuir isotherm model for both CF and POF. The most suitable ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Liu et al, [ 41 ] studied the adsorption of catechin onto cellulose, revealing that the adsorption capacities of cellulose for catechin were 2.70 and 2.82 mg/g at a pH of 2.0 and 7.0, respectively. Din et al [ 10 ] removed organic matter from river water using natural cellulose from coconut fiber and palm oil fiber via adsorption isotherm and kinetic studies, reporting the adsorption capacities achieved, which were 15.67 and 30.8 mg/g, respectively, suggesting that it is a suitable substrate for the retention of organic contaminants in an aqueous medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al, [ 41 ] studied the adsorption of catechin onto cellulose, revealing that the adsorption capacities of cellulose for catechin were 2.70 and 2.82 mg/g at a pH of 2.0 and 7.0, respectively. Din et al [ 10 ] removed organic matter from river water using natural cellulose from coconut fiber and palm oil fiber via adsorption isotherm and kinetic studies, reporting the adsorption capacities achieved, which were 15.67 and 30.8 mg/g, respectively, suggesting that it is a suitable substrate for the retention of organic contaminants in an aqueous medium.…”
Section: Resultsmentioning
confidence: 99%
“…Cellulose has been widely studied, and it has been reported that, in its natural state, it can retain various organic substances [ 10 , 11 ], i.e., aromatic compounds such as polyphenols that are present in vinasse [ 12 ]. On the other hand, cellulose can be easily structurally modified to enhance several physicochemical and functional properties.…”
Section: Introductionmentioning
confidence: 99%